Apuntes sobre la innovación educativa en el nivel universitario - Sebastián Martín Rinaldi; María Catalina Durand; Elaine Virginia Salas Urdaneta (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2021)
– In this paper, innovation in the university environment was approached based on a bibliographic and theoretical review that allowed the identification and description of the main aspects to be considered in the design and implementation of educational transformation projects. Innovation at the higher level is essential to develop quality training proposals, which contemplate all institutional areas and functions affected by the teaching-learning process and are adapted to the variable demands of the professional field. It is essential for any university to understand its components, the stakeholders' role, levels and possibilities of realization, especially in these times when innovation is at the centre of the educational scene. To conclude, some trends which incorporate new didactic strategies, monitoring modalities and technological mediations are presented, allowing the educational act to be carried out in an innovative way.
Keywords: 330; Innovación educativa; Calidad educativa; Universidad; Ense\~nanza -Aprendizaje; Educational innovation; Educational quality; University; Teaching -Learning